What is industry 5.0? The next manufacturing revolution / Rosliza Md Zani, Syukriah Ali and Mursyda Mahshar - Md Zani, Rosliza; Ali, Syukriah; Mahshar, Mursyda (Universiti Teknologi MARA, Kedah, 2022)
Industry 4.0, sometimes referred to as the Fourth Industrial Revolution, has been taking place around the globe since the middle of the 2010s. This revolution, according to the World Economic Forum (2017) is defined by the combination of artificial intelligence (AI), advanced robotics, additive manufacturing (3D printing), and the Internet of Things (IoT) to make manufacturing more efficient. Future industrial revolution is entering a new phase through machine learning and the skills it produces. Industry 5.0, as some experts have already named it, is well under way, with AIpowered platforms and tools have taken over the monotonous, low-value jobs that would otherwise reduce human productivity. Here’s the look and impact of Industry 5.0, and how machine learning is driving towards this change (Britt, 2022).